Avaliação química de solos tratados com vinhaça e cultivados com alfafa - Bianchi, Silmara Rossana (2008)
It is fundamental the presence of nutrients in the soil to assure its good quality and performance. If the soil is not able to supply the adequate levels of nutrients that the plants need to survive, these nutrients have to be added in the form of salts or organic fertilizers. Vinasse, the main residue produced during alcoholic distillation (13 liters of vinasse to 1 liter of produced alcohol), is mainly constituted of organic matter, elevate amount of nitrate and potassium, and it has been used as a substitute of mineral fertilizers. In this work, the use of sensors that select chemical such as nitrate, ammonium, potassium and phosphate and its associated instrumentation was evaluated in the soil s ions monitoring throughout growing doses of vinasse in an alfalfa culture by using in situ analyses. The vinasse additions effects in the soil s chemical characteristics, in the alfalfa production, and in the ions leaching were evaluated. The use of vinasse to replacement mineral fertilizer in the alfalfa production was also evaluated. During the experiments, performed in a greenhouse, vinasse doses corresponding to 0, 300, 400, 600, and 750 m3 ha-1 were applied in the clay soil (Orthic Ferralsol), and 0, 150, 300, 450, and 600 m3 ha-1 were applied in the sandy soil (Ustoxix Quatzipamment). Doses of 150 mg kg-1 of K as KCl and K2SO4 were provided as mineral fertilizers. The results indicated the viability of the use of sensors installed in the probe in the ions soil monitoring, except of ammonium, which sensor suffers interference of the high amount of potassium present in the vinasse. Multiparametric analysis of the results allowed the view of the qualitative effects of the different treatments. Soils treated with vinasse presented an increase in the potassium, calcium, and magnesium amount, in the exchanged cations capacity, in the bases saturation and in the pH. The foliar amount of potassium harvest in the two kinds of soils also increased, and the vinasse fertilization produced more dry matter when compared with the mineral KCl and K2SO4 treatments. The amount of nitrate and ammonium presented in the leached solution were higher than the allowed by the Conama 357.